The diagnostic efficacyof morphologicand Molecular methods in women with abnormal citology - Drumond, Denise G; Santos Jr., João Lúcio dos; Dôres, Gerson B; Gollner, Ângela Maria; Cupolilo, Sônia Maria N; JCoelho, Maria do Carmo; Castelo Filho, Adauto (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: cervical cancer is the most frequent neoplasia among the women of countries in development. Great part of these cases is caused by persistent infection with different types of human papilomavirus (HPV) classified as low and high risk, according to the risk of cervical cancer development. Objectives: based on women with abnormal cytology when screening for cervical cancer who were led from different units of the Public Health System to the reference university service and with a definite diagnosis of high cervical intraepithelial neoplasia or cancer, was to evaluate the diagnostic efficacy of morphologic and molecular methods used alone or together and the prevalence of HPV types 16, 18, 45, stratified into two age brackets. Methods: 167 women went to the Cervical Pathology and colposcopy clinic of the University Hospital of the Universidade Federal de Juiz de Fora, during the period from November 2002 to December 2003, with intact uterine cervix, not pregnant and without previous chemical and/or radiotherapy treatment for the inferior genital tract. Samples for cytology study were collected from all women, with conventional and liquid-based preparations, for CH2 for high risk virus, for DNA PAP and for Probe Pack test. The worst histologic diagnosis among the possible histologic studies through biopsy, conization or cirurgic pieces was considered as “gold standard”. Results: there is no difference regarding sensibility, positive predict value and negative predict value for all methods studied, However, the DNA PAP method has less specificities than the citology exam, either with conventional or based-liquid preparation. The prevalence of HPV 16, 18, 45 decreases from 88,9% to 50% in women of 30 years old or more, being this decrease statistically significant. Conclusion: in those women led to the PTGIC of the HU-UFJF with abnormal cytology it is not necessary to repeat any tests, just colposcopy in order to reach the final diagnosis.